Investigating the spatiotemporal distribution of fine particulate matter sources during persistent cold air pools in Salt Lake County - Jonathan Silberstein; Daniel Mendoza; Emma Rieves; Colleen E. Reid; Michael Hannigan (Atmospheric Environment: X)
Persistent cold air pools (PCAP), also referred to colloquially as inversions, are responsible for some of the greatest enhancements in air pollution in Utah’s Wasatch Front. PCAPs, which can last for a period of days or weeks, trap warm air beneath a layer of colder air, which results in the accumulation of particulates during the inversion. Fine particulate matter (PM2.5) sampling occurred in seven field sites across Salt Lake County (SLCo) during Wintertime (November–April). Concentrations of the organic mass of PM2.5 increased during inversion events (μinv = 4.0 μg/m3) when compared to the wintertime baseline (μbaseline = 3.5 μg/m3). However, organic mass enhancements during PCAPs were most pronounced at lowest-altitude field sites situated near potential PM2.5 sources. Four sources of organic carbon were identified, comprised of industrial, abrasive, wood burning, and onroad sources. During PCAP events, PM2.5 species profiles exhibited greater spatial heterogeneity, due to lower wind speeds and caps on vertical mixing (Coefficient of Determinationinv = 0.51, Coefficient of Determinationbaseline = 0.43). These results indicate both elevation and local source emissions may be of increased importance in understanding PM2.5 concentrations during PCAP events.